Income and poverty gaps between Han and ethnic minorities in rural China, 2002 and 2013 - Liu Xiaomin; Lidan Lu (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
In this chapter, using selected rural samples of the CHIP 2002 and CHIP 2013 surveys that cover a total of fourteen provinces, we focus on income and poverty differentiation among Chinese ethnic minorities and changes over time in atypical ethnic regions, that is, outside of China's five autonomous regions. As shown by our analysis as well as in other literature, the incomes of ethnic minorities have always been lower than those of Han. However, the income gap between ethnic minorities and Han narrowed during the 2002-2013 period in atypical ethnic areas. At the same time, it should be noted that during this period inequality increased more for ethnic minorities than it did for Han. Our decomposition of the inequality index shows that the income gap between Han and ethnic minorities can mainly be attributed to factors such as household characteristics and residence location rather than ethnic identity. Between 2002 and 2013 the pattern of poverty changed both for Han and ethnic minorities, but the changes in absolute poverty and relative poverty were the opposite. At the absolute poverty level, the poverty rate, poverty depth, and poverty strength narrowed. But in terms of relative poverty, the poverty rate, poverty depth, and poverty strength increased. Descriptive analysis reveals that ethnic differences in terms of poverty narrowed from 2002 to 2013. Regression analysis suggests that this might be attributed to the fact that ethnic minorities are mainly located in less-developed regions where their ethnic identity does not make any difference. In fact, when controlling for the regional variables, the level of poverty among Han is even more serious than that among ethnic minorities. It is also worth noting that the coefficient of education among ethnic minorities is significantly larger than that among Han, indicating that the development of education may be a very effective anti-poverty strategy for ethnic minorities.
Keywords: J15; P25; P36; 330; China; rural; poverty; ethnic minority